Peran Akuntansi Manajerial dalam Pengambilan Keputusan Strategis pada UMKM - Prasetyo, Andi (JIAKPRO: Jurnal Ilmiah Ilmu Akuntansi Profetik, 2025)
Managerial accounting plays a crucial role in supporting strategic decision-making in Micro, Small, and Medium Enterprises (MSMEs). In an increasingly competitive business environment, MSMEs face challenges in enhancing operational efficiency and competitiveness. Therefore, the application of effective managerial accounting can provide relevant and accurate information to support sound strategic decisions. Managerial accounting focuses on the collection, processing, and analysis of financial and non-financial data, helping management in planning, controlling, and evaluating performance. Strategic decisions involving resource allocation, product pricing, and market selection can be refined through the data provided by the managerial accounting system.This study aims to explore the contribution of managerial accounting to strategic decision-making in MSMEs. Through a qualitative approach and case studies, the research reveals that the proper implementation of managerial accounting can enhance cost efficiency, optimize resource utilization, and minimize the risk of losses. Moreover, the information generated by managerial accounting provides a solid foundation for determining strategic actions that can strengthen the MSMEs’ position in the competitive market. Therefore, strengthening the role of managerial accounting is crucial for the sustainability and growth of MSMEs